2002
DOI: 10.1068/a3537
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and the Multicultural City: Living with Diversity

Abstract: In the wake of the race disturbances in Oldham, Burnley, and Bradford in Summer 2001, the author explores the possibilities for intercultural understanding and dialogue. He argues that, although the national frame of racial and ethnic relations remains important, much of the negotiation of difference occurs at the very local level, through everyday experiences and encounters. Against current policy emphasis on community cohesion and mixed housing, which also tends to assume fixed minority ethnic identities, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
906
3
40

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,087 publications
(962 citation statements)
references
References 17 publications
13
906
3
40
Order By: Relevance
“…There was a rich body of literature around ethnic identity, diversity, hybridity, multiculturalism, cosmopolitanism, etc., including critical perspectives problematising these concepts and how they play out in society, but always and only embedded in the urban sphere (eg. Alexander, 2000;Amin, 2002; Back and Solomos, 2003;Brah,et al 1999;Hesse, 2000;Mirza, 1997;Parekh, 2000a;2000b). At the same time, especially within geography, there was interest in the ways in which rurality/rural space is implicated within national identity construction, notions of belonging and spatial practices 3 .…”
Section: Introductionmentioning
confidence: 99%
“…There was a rich body of literature around ethnic identity, diversity, hybridity, multiculturalism, cosmopolitanism, etc., including critical perspectives problematising these concepts and how they play out in society, but always and only embedded in the urban sphere (eg. Alexander, 2000;Amin, 2002; Back and Solomos, 2003;Brah,et al 1999;Hesse, 2000;Mirza, 1997;Parekh, 2000a;2000b). At the same time, especially within geography, there was interest in the ways in which rurality/rural space is implicated within national identity construction, notions of belonging and spatial practices 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Schools have been conceptualised as 'micropublic' spaces of interaction and intercultural engagement (Amin, 2002). They are a site where the 'local micropolitics of everyday interaction' (Vertovec 2007(Vertovec , p. 1046) take place and as such, they constitute the third layer of context studied in this paper.…”
Section: The School Context: Developing Emancipatory Representationsmentioning
confidence: 99%
“…This is evident through recent writings about cosmopolitanism, hospitality and new urban citizenship (e.g. Amin 2002, Bell 2007, Binnie et al 2006, Laurier & Philo 2006a/b, Iveson 2006, Wilson 2011.…”
mentioning
confidence: 99%
“…It is an issue that is particularly pertinent given rising levels of insecurity generated by post 9/11 terrorism and the current global financial crisis because in times of trouble attitudes towards minorities tend to harden. Given the implicit role of shared space in providing the opportunity for positive encounters between strangers, geography, urban studies and planning have paid increasing attention to this question, notwithstanding the longstanding interest of social psychologists in ÔcontactÕ theory (Allport 1954, Hewstone and Brown 1986) Here, some authors have observed the potential for ÔdifferenceÕ to be dissolved through a process of mixing and hybridisation of culture as a result of everyday encounters and interactions in public spaces (such as in cafes, on buses, at community events and sports clubs) where there is an accommodation of otherness because the proximity of strangers necessitates a pragmatic engagement across categorical boundaries (Amin 2002, Laurier & Philo 2006, Noble 2009, Wise 2009, Wilson 2011. Drawing on examples from a range of studies of hospitality spaces Bell (2007: 19) argues that food and eating create a feeling of being involved with others, providing consumers with a license to talk to each other which can facilitate positive encounters such that commensality Ôcan Ébe about social identification, the sharing of not only food and drink but also world views and patterns of livingÕ.…”
mentioning
confidence: 99%
See 1 more Smart Citation